Optimalisasi Penggunaan Media Ular Tangga Matematika dalam Menciptakan Pembelajaran Menyenangkan Bagi Siswa SD - Kenys Fadhilah Zamzam; Ririn Dwi Agustin; Asri Putri Anugraini (PT. Penerbit Riset Sadwa, 2026)
Mathematics learning in elementary schools is often considered complicated and uninteresting by students, resulting in low interest and enthusiasm for learning. This situation is also evident at Ulil Albab Elementary School in Kepanjen, where students tend to be inactive and less likely to participate in the learning process. Therefore, innovations in learning are needed to create a more engaging and interactive learning environment. This community service activity aims to maximize the use of the mathematical snakes and ladders media in creating a fun learning experience for elementary school students. The applied method is participatory and educational, with stages of preparation, implementation, evaluation, and follow-up. The practical process is carried out through educational games based on snakes and ladders combined with math problems. The results of this activity show an increase in student activity, motivation, and understanding of the mathematics material. Furthermore, students also showed a positive response to the learning experience. Thus, the use of the mathematical snakes and ladders media has proven successful in creating a fun learning experience and can be an innovative alternative in mathematics learning in elementary schools.